Organizational justice, work motivation, and organizational citizenship behavior (OCB) : their impact on commitment and employee performance - Tohara Tohara; Angelina Eleonora Rumengan; Indrayani Indrayani; Muammar Khaddafi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research method uses a causal model survey method using path analysis techniques. The research sample so that this study uses a saturated sample which is taken through the Census Technique using a simple random sample. The data collection technique used variable measurement using a questionnaire instrument. The results in this study The results of testing the path coefficient value indicate that the effect of OJ → Organizational Commitment is not significant. The results of the path coefficient test show that the effect of MK → Organizational Commitment is significant. The results of the path coefficient test show that the effect of OJ → Employee Performance is significant. The results of the path coefficient test show that the effect of MK → Employee Performance is not significant. The results of the path coefficient test show that the effect of KO → Employee Performance is not significant. The test results of the path coefficient value of the direct influence of OJ → Employee Performance is greater than the path coefficient value of the indirect influence of OJ → Organizational Commitment → Employee Performance. The results of testing the path coefficient value of the direct influence of MK→Employee Performance is smaller than the path coefficient value of the indirect influence of OJ→ Organizational Commitment→Employee Performance. The test results of the path coefficient value of OJ*OCB Moderation Effect→Employee Performance are not significant. The results of testing the path coefficient value of MK*OCB Moderation Effect→Employee Performance are not significant. The test results of the path coefficient value of the Moderation Effect KO*OCB→Employee Performance are not significant.